Stimuli‐responsive poly(hydroxyethyl methacrylate) hydrogels from carboxylic acid‐functionalized crosslinkers. Issue 9 (21st May 2019) - Bingol, H. Betul; Agopcan‐Cinar, Sesil; Bal, Tugba; Oran, D. Ceren; Kizilel, Seda; Kayaman‐Apohan, Nilhan; Avci, Duygu
Abstract: Tailoring hydrogel properties by modifications of the crosslinker structure is a good method for the design of hydrogels with a wide range of properties. In this study, two novel carboxylic acid‐functionalized dimethacrylate crosslinkers (1a and 2a) are synthesized by the reaction of poly(ethylene glycol) or 2‐hydroxyethyl disulfide with tert ‐butyl α‐bromomethacrylate followed by cleavage of tert ‐butyl groups using trifluoroacetic acid. Their copolymerization reactivity with 2‐hydroxyethyl methacrylate (HEMA) investigated by photopolymerization studies performed on photo‐differential scanning calorimetry shows higher reactivity of 2a compared to 1a. These crosslinkers are then used at different ratios for fabrication of pH‐ and redox‐responsive poly(2‐hydroxyethyl methacrylate)‐based hydrogels. The swelling behavior of the hydrogels is found to be dependent on the structure of the crosslinker, degree of crosslinking, pH, and CaCl2 concentration. The redox‐responsive behavior is demonstrated by degradation of the hydrogel upon exposure to 1, 4‐dithiothreitol. The dye Rhodamine 6G and the drug resorcinol are used as models to demonstrate the pH and redox dependent release of loaded compounds from the hydrogels. The electrostatic interactions between the carboxylate groups and the positively charged R6G are found to govern the release profile in DTT and counteract the diffusion of dye molecules and significant amount of release (79% in 120 hr) occurs only at highly acidic conditions. The degradation mediated release in DTT is observed better in case of resorcinol (around 88% in 5 hr). Overall, these hydrogels can be regarded as good candidates for several applications, such as matrices for controlled release, tissue repair, and regeneration.